Potassium Fertilization of Eucalyptus in an Entisol in Low-Elevation Cerrado - Gazola, Rodolfo de Niro [UNESP]; Buzetti, Salatier [UNESP]; Minhoto Teixeira Filho, Marcelo Carvalho [UNESP]; Dinalli Gazola, Raissa Pereira [UNESP]; Celestrino, Thiago de Souza [UNESP]; Silva, Alexandre Costa da [UNESP]; Muller da Silva, Paulo Henrique (Soc Brasileira De Ciencia Do Solo, 2019)
Potassium (K) is one of the most highly accumulating nutrients in Eucalyptus and, consequently, is heavily exported by the harvesting of wood. Moreover, its availability in the soil in most Brazilian plantation areas is very low, especially in the regions of the Cerrado biome, which has soils with low natural fertility and marked water deficits, implying a lack of nutrient supply and, consequently, a less efficient water use. Our objective was to evaluate the effects of K fertilization on Eucalyptus biomass yield, the addition of nutrients to the soil by leaf deposition, nutrient use efficiency, and soil K availability. The experiment was conducted with clone I144 (Eucalyptus urophylla) in the municipality of Tres Lagoas/MS, in a Neossolo Quartzarenico Ortico (Entisol). The experimental design was a randomized block with four treatments and five replicates. The treatments consisted of four K doses (0, 90, 135, and 180 kg ha(-1) of K2O) as KCl. Plant biomass production (leaves, branches, trunk, and bark), senescent leaf deposition, leaf nutrient concentrations, nutrient accumulation in the different plant compartments, nutrient use efficiency, addition of nutrients to the soil by leaf deposition, and soil K availability were evaluated. Potassium fertilization increased the biomass yield of Eucalyptus plants, senescent leaf K content, the transfer of K to the soil, the accumulation of K in the aerial plant parts, and the K content in the soil. However, it did not influence senescent leaf deposition yield or plant K use efficiency.
Keywords: senescent leaf nutrients; fertilization; biomass; macronutrients; nutritional efficiency